HELICAL TUBE HEAT EXCHANGER DESIGN FOR MILK PASTEURIZATION PROCESS WITH HIGH TEMPERATURE SHORT TIME: English - Kharisma , Aji Abdillah; Sari, Sri Poernomo; Suhada , Mochammad Fiqri (Jurnal Rekayasa Mesin, 2025)
The most common issue facing by the beverage industry is to maintain the cleanliness of a product. It is very important to note, especially for milk pasteurization process to kill bacteria, thus a heat exchanger is required. Heat exchanger is a device that allows heat transfer between two fluids of different temperatures. The purpose of this research is to design a helical tube heat exchanger, where this heat exchanger is focused on the heating process in milk pasteurization process. The designed tube is a helical model for the flow of milk fluid. The research method is carried out by designing a helical tube heat exchanger and performing simulations and mathematical calculations on the heat transfer. After simulation using software assistance and mathematical calculations, resulting shell length is 1.5 m, helical tube length is 6.4 m, shell diameter is 0.3 m and helical tube diameter is 0.023 m, totaling three pieces each. The shell utilized 304 stainless steel material and the helical tube used copper material which aims to improve the heat transfer process. The operating principle of this heat exchanger is as a heat exchange medium for milk fluid, the process will be carried out by this heat exchanger is the milk pasteurization process. The milk pasteurization method carried out in this final project is the higher temperature short time (HTST) method, which is the process of heating the milk fluid by producing milk outlet between 70oC – 75oC  for 15 seconds.